Search for a light charged Higgs boson in the decay channel H+ -> c(s)over-bar in t(t)over-bar events using pp collisions at root s=7 TeV with the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; et al. (2013)
A search for a charged Higgs boson (H +) in tt̄ decays is presented, where one of the top quarks decays via t→H + b, followed by H +→ two jets (cs̄). The other top quark decays to Wb, where the W boson then decays into a lepton (e/μ) and a neutrino. The data were recorded in pp collisions at √s = 7 TeV by the ATLAS detector at the LHC in 2011, and correspond to an integrated luminosity of 4.7 fb-1. With no observation of a signal, 95 % confidence level (CL) upper limits are set on the decay branching ratio of top quarks to charged Higgs bosons varying between 5 % and 1 % for H + masses between 90 GeV and 150 GeV, assuming B(H+ → cs̄ = 100 %. © 2013 CERN for the benefit of the ATLAS collaboration.